1999
DOI: 10.1213/00000539-199906000-00009
|View full text |Cite
|
Sign up to set email alerts
|

The Direct Effects of Heparin and Protamine on Canine Tracheal Smooth Muscle Tone

Abstract: Heparin and protamine are used for cardiopulmonary bypass in cardiac surgery; however, the direct effects and mechanisms of these drugs on airway smooth muscle tone are still not fully known. We investigated the in vitro effects of these drugs on canine tracheal smooth muscle by measuring the muscle tension and intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) and by measuring inward Ca 2ϩ currents (I Ca ) through voltage-dependent Ca 2ϩ channels.[Ca 2ϩ ] i was monitored by the 500-nm light emission ratio of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…74,79 Such effects asthma in a small, subjectively assessed trial in 1960 are unlikely to be attributable to direct relaxant effects and was found to be ninety percent effective in proon smooth muscle as heparin has no effect on isolated viding relief of symptoms, when administered intraairway smooth muscle contractions elicited by musvenously. 61 carinic agonists, [80][81][82][83] although antigen-induced conMore recently, heparin delivered by inhalation was traction in airway smooth muscle from immunised found to prevent reduction in specific airway consheep is sensitive to heparin, 81 further supporting the ductance in subjects with exercise-induced asthma. [62][63][64] hypothesis that the acute bronchoprotective actions of this molecule are mediated through effects on mast In atopic asthmatics, a single inhaled dose of heparin …”
mentioning
confidence: 99%
“…74,79 Such effects asthma in a small, subjectively assessed trial in 1960 are unlikely to be attributable to direct relaxant effects and was found to be ninety percent effective in proon smooth muscle as heparin has no effect on isolated viding relief of symptoms, when administered intraairway smooth muscle contractions elicited by musvenously. 61 carinic agonists, [80][81][82][83] although antigen-induced conMore recently, heparin delivered by inhalation was traction in airway smooth muscle from immunised found to prevent reduction in specific airway consheep is sensitive to heparin, 81 further supporting the ductance in subjects with exercise-induced asthma. [62][63][64] hypothesis that the acute bronchoprotective actions of this molecule are mediated through effects on mast In atopic asthmatics, a single inhaled dose of heparin …”
mentioning
confidence: 99%
“…In contrast, it has been shown that both protamine and the heparin±protamine complex can inhibit canine tracheal smooth muscle contraction by decreasing [Ca 2+ ] i in vitro. 19 These agents decrease the agonist-induced increase in [Ca 2+ ] i by inhibition of VDCCs. 19…”
Section: Effects Of Other Anaesthetic Agents On Airway Smooth Musclementioning
confidence: 99%